S108 Using forward genetic screens and novel human alveolar organoid models to study surfactant protein C trafficking in heath and disease. (11th November 2022) - Rutherford, EN; van den Boomen, D; Lim, K; Lehner, PJ; Rawlins, EL; Marciniak, SJ; Dickens, JA
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) is a fatal disease of lung parenchymal scarring triggered by alveolar epithelial cell dysfunction. Inherited forms of pulmonary fibrosis, including those caused by mutant forms of surfactant protein C (SFTPC), offer an opportunity to study early pathogenic events which remain poorly understood. Objectives: We wished to interrogate specific factors involved in SFTPC trafficking to understand the pathological mistrafficking phenotype caused by the commonest pathogenic mutant, SFTPC-I73T, which aberrantly localises to the plasma membrane. Methods: CRISPR-Cas9 forward genetic screens were employed in an immortalised cell model system to interrogate SFTPC processing and trafficking and a FACS-based readout used to identify altered SFTPC localisation. Alveolar organoids derived from human embryonic lung tissue were transduced with an inducible CRISPRi system for the validation of screen hits. Results: We identified several novel targets including candidate proteases and ubiquitin ligases in addition to validating core complexes suspected to be involved in SFTPC trafficking. Of particular note is the E3 ligase ITCH which, when depleted, altered SFTPC localisation in a manner that phenocopies the pathogenic I73T mutant. Further validation is underway using genetic manipulation of a novel human embryonic alveolar organoid system. Conclusions: A cell line model of SFTPC trafficking has allowed us to identify important factors in SFTPC trafficking using forward genetic screens which we can test in a physiological system to understand SFTPC handling in health and disease.